Here to Last? Evaluating the Impact of Business Factors on Startup Constancy - Witham, Adam; Pendleton, Taylor (Journal of Entrepreneurship, Business and Economics; Vol 12 No 1 (2024), 2024)
The purpose of this article is to analyze how entrepreneurial constancy is affected for private-sector firms of varying maturities. As the entrepreneurial ecosystem in a state affects firms differently based on their age, we construct an empirical model of constancy. This article compiles annual data by state from 2001-2020 on compensation, constancy, contribution, and creation by firm age (0-1 years, 2-3 years, 4-5 years, 6-10 years, 11+ years) as well as measures of economic freedom and annual average unemployment rates. We then use OLS estimation to model constancy of firms in the private sector by firm age. Regardless of the maturity of firms, whether startups or firms aged 11+ years, compensation produces a positive, statistically significant effect on constancy. We further observe that increases in economic freedom and unemployment rates lead to increases in constancy for startup firms in the private sector. This article adds to the business and entrepreneurship literature through both its disaggregated analysis by firm age and its regression analysis in modeling constancy. Research Paper Keywords: Constancy, Firm maturity, Economic freedom, Kauffman, State Business Environment, Startups Reference to this paper should be made as follows: Witham, A., & Pendleton, T. (2024). Here to Last? Evaluating the Impact of Business Factors on Startup Constancy. Journal of Entrepreneurship, Business and Economics , 12 (1), 66–87.